Neovascular glaucoma following central retinal vein occlusion - a case report - Budihardjo, Budihardjo (Universitas Gadjah Mada, 1998)
Glaucoma is an Important cause of blindness, in particular neovascular glaucoma which is a complex condition and always becomes challenging for the clinician in the past, present and the future. A 54-year-old man suffering from blindness of neovascular glaucoma following central retinal vein occlusion in the right eye with no response to Pan Retinal Photocoagulation (PRP) and open angle glaucoma in the left eye has been reported. Systemic conditions as a predisposing factor were not found, so the local ocular background i.e open angle glaucoma was suspected to be the cause of central retinal vein occlusion. In this case the management must be focused on the left eye to avoid further complication. The right eye was on end stage and no response to PRP and the visual acuity Is no light perception (NLP). Enucleation should be considered as the high intraocular pressure (IOP) and ocular pain persisted.Key words: neovascular glaucoma - central retinal vein occlusion - open angle glaucoma - Pan retinal photocoagulation